Bradykinin system is involved in endometriosis‐related pain through endothelin‐1 production. (16th October 2017) - Yoshino, O.; Yamada‐Nomoto, K.; Kobayashi, M.; Andoh, T.; Hongo, M.; Ono, Y.; Hasegawa‐Idemitsu, A.; Sakai, A.; Osuga, Y.; Saito, S.
Abstract: Background: Endometriosis is a gynaecological disease exhibiting severe pelvic pain, but the mechanism of pain production remains unknown. Bradykinin (BK) is known as an inflammatory mediator, and shows elevated levels in inflammatory diseases such as rheumatoid arthritis. In the present study, we evaluated whether BK is involved in endometriosis‐related pain. Methods: Endometriotic lesions were used for immunohistochemistry. Primary cultures of endometriotic stromal cells (ESC) were stimulated with IL‐1β and/or BK. Quantitative RT‐PCR was used to evaluate the mRNA expressions of BK receptors (BKR) and endothelin‐1 in ESC. The concentration of endothelin‐1 in cystic fluid of endometrioma or non‐endometrioma was measured with ELISA. The conditioned medium of ESC stimulated with IL‐1β and/or BK was injected intraplantarly in mice, and evaluated whether pain‐related licking behaviour was elicited. Results: The expressions of BK and BKR in endometriotic lesions were observed by immunohistochemistry. In vitro experiments showed that IL‐1β induced BKR‐B1 and B2 on ESC. Activation of these receptors by BK significantly induced endothelin‐1 expression in ESC, which was negated completely by HOE‐140, a BKR‐B2 antagonist. The cystic fluid of endometrioma contained higher amount of endothelin‐1 compared to non‐endometrioma. Intraplantar injection of the conditioned medium of ESC treated with IL‐1β and BK significantly induced licking behaviour, which was suppressed with BQ‐123, an endothelin type‐A receptor antagonist. Conclusions: The present study demonstrated the presence and the function of the BK axis in endometriosis, and established a potential new therapy target for endometriosis‐related pain. Significance: The present study demonstrated (1) the presence and the function of the BK system in endometriosis, (2) activation of BKR induced endothelin‐1 in endometriotic lesion and (3) blocking endothelin‐1 was effective to decrease pain.